Koleksi buku cerita bergambar (picture storybooks) di Perpustakaan Desa Sukamukti - Pawit M. Yusup; Tine Silvana Rachmawati; Ninis Agustini Damayani; Evi Nursanti Rukmana (Berkala Ilmu Perpustakaan dan Informasi, 2020)
Introduction. The teachers at Kelompok Belajar Islam Terpadu (KBIT) Sukamukti village have used picture storybooks from the Library of Sukamukti village and reading them in a story telling session to their students. Two of this activities as a basic in the pre-reading activity to early childhood, so that the purpose this reaserch is to understand how the teachers use the picture storybooks, reading technique, and storytelling. Data Collection Method. This paper used a qualitative perspective with phenomenology by using observations, interviews, focus group discussions, and literature study. Analysis Data. Data from interviews were transcribed for further analysis Results and Discussion. The teachers at KBIT Sukamukti village used the picture of storybooks with fables. The teachers also discussed plot, animal activities, themes and morality based on the story. The language in the story is easy to understand by the children, book illustrations explain the reality of the character in the forest. Activities read aloud by introducing the identity of the book used, and storytelling activities through self-assement, stories, sounds, expressions, gestures, and other abilities. Conclusion. The teachers read and tell stories to educate young children in alphabet, vocabularies, and creativity. This helps early children in the process of learning pre-reading.